(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Attaining the prompts and cost-effective execution of a project presents remarkable challenge, which is the key factors of adequate planning and scheduling of the project. This research categorically focus on finding a balance between the cost of project and the minimizing expected time needed for the conclusion of a construction project. Data were collected from the Building Practice Ltd., a construction firm situated in Lagos State, Nigeria. The finding adopted both the Programme Evaluation and Review Techniques (PERT) and Critical Path Method (CPM). Analysis was carried out, the possible routes of the activities involved in the building project, location of critical path and expected duration for every activity in the building project was determined. The probability of completing the project within the specific time was evaluated and the result indicated that there is a 50% chance for the projected to be executed within the specify period. The project was delayed due to inadequate equipment, loss of weeks as a result of changing in plan and insufficient manpower. The initial completion and actual completion time was estimated to be two months difference which actually reduce the time and increase cost efficiency of the project.